MODEL BIOPHILIC SPACES FOR WASTE MANAGEMENT AT THE HOUSEHOLD LEVEL - M.S.S. MAHALAKSHMI*; S. VISALAKSHI RAJESWARI (The Journal of Research ANGRAU, 2023)
Biodegradable organic waste that come from kitchen and retentate, the waste from reverse osmosis water purifier have become a significant concern to the environment pollution. In order to reclaim and recylce the wastes, the experimental study was carried out during the pandemic period from March 2020 to October 2020 in the peri-urban area of Coimbatore. The sampling method adopted was purposive. The women-centred environmental strategy of utilizing household wastes (through vermicompost and hydroponics) and converting them into eco-friendly, viable economic products were attempted. The experimental study infers that on an average 5.73 ± 0.62 kilograms of vermicompost was harvested in every batch in two months period.The ratio of decomposed wastes to vermicompost realized was 46:100. The experimental study conducted to upcycle the retentate adopting hydroponic technology showed a good result, and it promoted biophilic spaces in the microenvironment, consuming less space. This research showcased few model biophilic spaces tried and used to promote hydroponic technology and successfully display waste management approaches.